2013
DOI: 10.1371/journal.pone.0058654
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Prevalence among Migrants in the US Compared to the US-Born and the Population in Countries of Origin

Abstract: ObjectivesSmoking among migrants is known to differ from the host population, but migrants’ smoking is rarely ever compared to the prevalence of smoking in their country of origin. The goal of this study is to compare the smoking prevalence among migrants to that of both the US-born population and the countries of origin. Further analyses assess the influence of sex, age at time of entry to the US and education level.MethodsData of 248,726 US-born and migrants from 14 countries were obtained from the Tobacco U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 20 publications
11
43
1
Order By: Relevance
“…ARIBs' use of tobacco, cannabis and stimulants has increased, as have use of these substances in the country-of-origin population, especially the latter two. This positive correlation was not found in the US for tobacco (Bosdriesz et al, 2013), but is consistent with studies showing that non-mixed first-generation adolescents from developing countries have lower substance use, especially alcohol, tobacco and cannabis, than AAs, whereas those from wealthier countries like Non-Eastern Europeans have similar use (Amundsen et al, 2005;Amundsen, 2012;Hjern and Allebeck, 2004;Koya and Egede, 2007;SAMHSA, 2011). …”
Section: Disentangling Effects Of Immigration-related Factors On Subssupporting
confidence: 81%
See 1 more Smart Citation
“…ARIBs' use of tobacco, cannabis and stimulants has increased, as have use of these substances in the country-of-origin population, especially the latter two. This positive correlation was not found in the US for tobacco (Bosdriesz et al, 2013), but is consistent with studies showing that non-mixed first-generation adolescents from developing countries have lower substance use, especially alcohol, tobacco and cannabis, than AAs, whereas those from wealthier countries like Non-Eastern Europeans have similar use (Amundsen et al, 2005;Amundsen, 2012;Hjern and Allebeck, 2004;Koya and Egede, 2007;SAMHSA, 2011). …”
Section: Disentangling Effects Of Immigration-related Factors On Subssupporting
confidence: 81%
“…The fact that ARIBs' risk was influenced considerably more by country-of-origin characteristics and by both parents being foreign-born than being a foreign-born adolescent suggests that parental and ethnic transmission of norms and values may have as much or more importance in determining ARIBs' substance use than host-country exposure, supporting theories claiming that PRIBs maintain for quite a long time cultural norms and behaviors from their country-of-origin (segmented assimilation, transnationalism), which may even pass on to their host-country-born descendants (Bosdriesz et al, 2013;Cook and Caetano, 2014). Parental culture probably strongly influences the main factors mediating immigration effects on substance use as does the choice of peers with whom ARIBs associate (Blake et al, 2001;Prado et al, 2009).…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Recent studies have found that foreign-born Asian immigrants' smoking rate is lower than the general United States population [12][13][14][15]. For instance, in Baluja, Park, and Myers' study [13], they reported that in years 1995-1996 and 1998-1999, foreign-born Asian immigrants smoking rate was 11.8 %, whereas the smoking rate of native-born (all races combined) was 22.6 %.…”
Section: Introductionmentioning
confidence: 98%
“…However, these studies were all cross-sectional, which only examined the phenomena at one point in time. Critics argued that the low smoking rate of Asian immigrants was only temporary [14]. To test the extent of HME on Asian immigrants' smoking behavior, a longitudinal study provides more reliable evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the participants in this survey claimed they do not smoke and drink (Table 5a. may contribute to the lower tobacco consumption among migrants than counterparts in the new country and in the country of origin (202). Reported alcohol use was also found to be lower in migrants than in the general population in Sydney (203).…”
Section: Drinking and Smokingmentioning
confidence: 99%